2023
DOI: 10.1590/1678-7757-2022-0404
|View full text |Cite
|
Sign up to set email alerts
|

C5aR antagonist inhibits LPS-induced inflammation in human gingival fibroblasts via NF-κB and MAPK signaling pathways

Abstract: Objective: Abnormal complement activation is associated with periodontitis. W54011 is a novel non-peptide C5aR antagonist (C5aRA) that exhibits favorable anti-inflammatory effects in various inflammatory models. However, whether W54011 inhibits periodontitis has not yet been fully elucidated. To address this, we have investigated the probable antiinflammatory mechanism of W54011 in LPS-treated inflammation in human gingival fibroblasts (HGFs). Methodology: HGFs were isolated from healthy gingival tissue sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…TLR4 is a transmembrane protein that plays a role in early pathogen recognition and innate immunity. Activation of this receptor induces the activation of downstream transcription factors such as NF-κB, which further enhances the production of pro-inflammatory factors including IL-1β and TNF-α, thereby promoting the inflammatory response to indirectly improve the immune response [ 51 ]. Huang et al found that acute exposure to OBS (30 mg/L) significantly increased the expression levels of immune-related proteins (IL-1β, CXCL8, MMP9, Casp8) in zebrafish larvae, and was generally consistent with the transcriptomic results [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 is a transmembrane protein that plays a role in early pathogen recognition and innate immunity. Activation of this receptor induces the activation of downstream transcription factors such as NF-κB, which further enhances the production of pro-inflammatory factors including IL-1β and TNF-α, thereby promoting the inflammatory response to indirectly improve the immune response [ 51 ]. Huang et al found that acute exposure to OBS (30 mg/L) significantly increased the expression levels of immune-related proteins (IL-1β, CXCL8, MMP9, Casp8) in zebrafish larvae, and was generally consistent with the transcriptomic results [ 43 ].…”
Section: Discussionmentioning
confidence: 99%